Repair analysis of Pinang Bridge oprit subsidence with mortar form using LISA FEA - Efendi, Aco Wahyu (Journal of Research and Inovation in Civil Engineering as Applied Science (RIGID), 2022)
Mortar foam is one of the best alternatives to embankment soil, with a smaller load and very fast work, the use of this technology has been applied in several locations with small soil bearing capacity and requires time and cost efficient repairs, foam mortar has been used under construction of a road in Central Kalimantan and is still in good condition. This research was carried out to make improvements with the help of the Finite element method software using LISA FEA V.8. It may offer great information in calculating the stress levels that happen in the elements examined linearly and nonlinearly when examining the behavior of elements. For the selection of a very good oprit material, it tends to use mortar foam material because the material has contributed significantly to the carrying capacity of the oprit where from the deformation analysis and also the stresses that occur, the mortar foam material provides a fairly small deformation.